HUBUNGAN KERJA PEMERINTAH DESA DENGAN LEMBAGA ADAT DALAM PENGELOLAAN KEKAYAAN DESA DI DESA LUBUK SIAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Data Wardana; Yendri Nazir (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
The 1945 Constitution of the State of the Republic of Indonesia opens the possibility of a government structure within the Indonesian system of government. Then the existence of the village is very important in the implementation of the government and in order to realize the National goal. Besides, the village is the leading structure of the government as the spearhead of the success of national development and development carried out by Desa Itu Sendiri. One of these villages is Lubuk Siam Village, Siak Hulu District, Kampar District. In the execution of development in the village using village funds and village income. However, in practice, the original income of Lubuk Siam village was accepted by the adat institution so that the original income of the village was 0 (zero) rupiah. While villages have original source of village income comes from third party donations, lake management and other legitimate income. This study aims to find out how the working relationship of village government with village customary institution in Lubuk Siam village Siak Hulu subdistrict of Kampar regency. To know the system of management of original income of village (PAD) of Lubuk Siam village of Siak Hulu district Kampar regency. The method used in this research is qualitative with the technique of data collection is observation, interview and documentation. As for the informant of the research are Village Head, Customary Institution, Chairman of BPD and Community Leaders and Village Treasurer. The result of the research is the working relationship of the Data Institution with the Village Government in the management of village wealth is first: the partnership relationship in the sense of equally managing the income of the village, the coordination relationship with the deliberation and the social control relationship in which the adat institution oversees the use of the fund. While the management system is received by customary institutions and managed by the village government for village development activities. From the result of the research, it can be concluded that the original village revenue management system of lubuk siam is not in accordance with the applicable regulations because the adat institution is not regulated by its authority in the management of village's wealth. To be supervised by the government in this case Kampar regency government. In order that the management does not violate the rules, the village of Lubuk Siam Subdistrict Siak Hulu proposed to be a traditional village.